The Reality of Physical Restraint Implementation During Hospitalization in Older Patients With Hip Fractures - Sho Fujita MD; Takehiro Michikawa MD; Takumi Taniguchi MD; Takayuki Hirono MD; Keigo Sato MD; Soya Kawabata MD; Takao Tobe PhD; Risa Tobe Pharm.D; Mitsuhiro Morita MD; Shigeki Yamada PhD; Nobuyuki Fujita MD (Geriatric Orthopaedic Surgery & Rehabilitation)
Introduction Hip fractures, which result in a high rate of complications and mortality, are a major public health concern in aging societies. Physical restraint for older patients with hip fractures may be employed to ensure safety, continue medical treatment, and minimize the risk of harm to oneself or others. This study aimed to investigate the current practices of physical restraint use among hip fracture patients across 2 acute-care hospitals, as well as uncover factors associated with physical restraint in patients with hip fracture. Methods We retrospectively reviewed all patients aged ≥65 years who underwent surgery for hip fractures at two institutions. Physical restraint was applied in accordance with institutional guidelines, following thorough assessments by physicians and nurses and obtaining informed consent from the patient or their family. When we examined the independent associations of physical restraint during hospitalization, the Poisson regression models were used to estimate the relative risks (RRs) and 95% confidence intervals (CIs). Results In total, 463 older patients with hip fractures were assessed. Among the included patients, 118 (25.5%) were subjected to physical restraint. Multivariable analysis revealed that 85 years or older (RR, 1.8; CI: 1.1–3.0), a BMI below 18.5 (RR, 1.8; CI: 1.4–2.5), dementia (RR, 2.3; CI: 1.7–3.1), stroke (RR, 1.5; CI: 1.1–2.0), impairment in physical function (RR, 3.1; CI: 1.2–8.3), and administration of antipsychotics (RR, 1.6; CI: 1.0–2.4) were significantly associated with the implementation of physical restraint. Conclusions This retrospective study provided real-world data regarding the use of physical restraint in older patients with hip fractures. Patients with older age, low BMI, dementia, stroke, impaired physical function, and administration of antipsychotics may be at high risk for the use of physical restraints. To minimize the use of physical restraints, future research for further data collection will be essential.